Animal fiber characterization and fiber loading effect on mechanical behaviors of sheep wool fiber reinforced polyester composites - J. Manivannan; S. Rajesh; K. Mayandi; N. Rajini; Sikiru Oluwarotimi Ismail; Faruq Mohammad; Manja Kitek Kuzman; Hamad A. Al-Lohedan (Journal of Natural Fibers, 2022)
This study presents animal fiber characterization and the influence of various fiber loadings on mechanical properties of sheep hair fiber-reinforced polymer (SHFRP) composites. The sheep hair fibers (SHF) characterization was carried out using X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FTIR), thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM) and non-contact surface roughness machine. The functional group and chemical bond were analyzed using FTIR techniques. The crystallinity index and thermal stability of the SHF were characterized, using XRD and TGA techniques, respectively. The composites were fabricated using a compression molding technique and a varying weight percentage of 20, 30 and 40 fiber. The composite plates were cut into test samples according to ASTM standard methods for their mechanical (tensile, flexural and impact) behaviors to be extensively analyzed. The surface morphology of the fractured samples was examined with aid of an SEM. From the results obtained, it was evident that the SHFRP composite recorded a significantly increased tensile strength property when fiber loading was increased from 20 to 40 wt%. The optimum 40 wt% SHFRP composite sample recorded better flexural and impact strength, when compared with other counterparts. This was attributed to a better fiber-matrix interfacial adhesion, as established fromSEM micrographs.